Synthesis of new Mn19 analogues and their structural, electrochemical and catalytic properties. Issue 15 (19th February 2019) - Chevallot-Beroux, Elodie; Ako, Ayuk M.; Schmitt, Wolfgang; Twamley, Brendan; Moran, Joseph; Corinne, Boudon; Ruhlmann, Laurent; Mameri, Samir
Abstract : We report the synthesis, structural characterisation, electrochemistry and catalytic activity in the selective oxidation of benzyl alcohol of new Mn19 and Mn18 M analogues: [MnIII12MnII7(μ4 -O)8 (μ3 -OCH3 )2 (μ3 -Br)6 (HL Me )12 (MeOH)6 ]Br2 (2 ) and [MnIII12MnII6Sr(μ4 -O8 (μ3 -Cl)8 (HL Me )12 (MeCN)6 ]Cl2 cluster (3 ), where H3 L Me is 2, 6-bis(hydroxymethyl)- p -cresol. Abstract : We report the synthesis and structural characterisation of new Mn19 and Mn18 M analogues, [MnIII12MnII7(μ4 -O)8 (μ3 -OCH3 )2 (μ3 -Br)6 (HL Me )12 (MeOH)6 ]Br2 (2 ) and [MnIII12MnII6Sr(μ4 -O8 (μ3 -Cl)8 (HL Me )12 (MeCN)6 ]Cl2 cluster (3 ), where H3 L Me is 2, 6-bis(hydroxymethyl)- p -cresol. The electrochemistry of2 and3 has been investigated and their activity as catalysts in the oxidation of benzyl alcohol has been evaluated. Selective oxidation of benzyl alcohol to benzaldehyde by O2 was achieved using 1 mol% of catalyst with conversions of 74% (2 ) and 60% (3 ) at 140 °C using TEMPO as a co-catalyst. No partial conversion of benzaldehyde to benzoic acid was observed. The results obtained revealed that different operative parameters – such as catalyst loading, temperature, time, solvent and the presence of molecular oxygen – played an important role in the selective oxidation of benzyl alcohol.